2022
DOI: 10.3390/en15093167
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Capability of PD-Type Recognition Based on UHF Signals Recorded with Different Antennas Using Supervised Machine Learning

Abstract: The article presents research on the influence of the type of UHF antenna and the type of machine learning algorithm on the effectiveness of classification of partial discharges (PD) occurring in the insulation system of a power transformer. For this purpose, four antennas specially adapted to be installed in the transformer tank (UHF disk sensor, UHF drain valve sensor, planar inverted F-type antenna, Hilbert curve fractal antenna) and a reference log-periodic antenna were used in laboratory tests. During the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…A similar work was reported in [38]. Besides, other feature extraction methods based on time-frequency transformation can also be found in [39], [40], [41], [42], and [43], interested readers can refer to the original articles for more details.…”
Section: ) Transform Domain-based Featuresmentioning
confidence: 76%
See 1 more Smart Citation
“…A similar work was reported in [38]. Besides, other feature extraction methods based on time-frequency transformation can also be found in [39], [40], [41], [42], and [43], interested readers can refer to the original articles for more details.…”
Section: ) Transform Domain-based Featuresmentioning
confidence: 76%
“…In [55], a sequential feature selection algorithm namely MRMR was used to select a 18-D feature subset from the original 84-D feature vector for subsequent PD classification step. Similar feature selection scheme was also adopted in [43], and the authors demonstrated that using only the first feature indicated by the MRMR algorithm was sufficient for accurate recognition of UHF PD signals.…”
Section: ) Feature Selection Algorithmsmentioning
confidence: 99%
“…A negative relationship occurs when the value of the feature increases, and then it decreases the other or vice versa. Zero correlation is observed when one feature does not affect the other [51]. The analysis of the correlation between all the features by tuning the Pearson's coefficient is in Equation ( 2), which describes the coefficient for tuning all the features.…”
Section: Correlation Featuresmentioning
confidence: 99%